E. Coli cytotoxic necrotizing factor-1 promotes colorectal carcinogenesis by causing oxidative stress, DNA damage and intestinal permeability alteration - Michela Tozzi; Alessia Fiore; Sara Travaglione; Francesca Marcon; Gabriella Rainaldi; Elena Angela Pia Germinario; Ilenia Laterza; Simona Donati; Daniele Macchia; Massimo Spada; Omar Leoni; Maria Cristina Quattrini; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Bacterial toxins are emerging as promising hallmarks of colorectal cancer (CRC) pathogenesis. In particular, Cytotoxic Necrotizing Factor 1 (CNF1) from E. coli deserves special consideration due to the significantly higher prevalence of this toxin gene in CRC patients with respect to healthy subjects, and to the numerous tumor-promoting effects that have been ascribed to the toxin in vitro. Despite this evidence, a definitive causal link between CNF1 and CRC was missing. Here we investigated whether CNF1 plays an active role in CRC onset by analyzing pro-carcinogenic key effects specifically induced by the toxin in vitro and in vivo. Methods Viability assays, confocal microscopy of γH2AX and 53BP1 molecules and cytogenetic analysis were carried out to assess CNF1-induced genotoxicity on non-neoplastic intestinal epithelial cells. Caco-2 monolayers and 3D Caco-2 spheroids were used to evaluate permeability alterations specifically induced by CNF1, either in the presence or in the absence of inflammation. In vivo, an inflammatory bowel disease (IBD) model was exploited to evaluate the carcinogenic potential of CNF1. Immunohistochemistry and immunofluorescence stainings of formalin-fixed paraffin-embedded (FFPE) colon tissue were carried out as well as fecal microbiota composition analysis by 16 S rRNA gene sequencing. Results CNF1 induces the release of reactive oxidizing species and chromosomal instability in non-neoplastic intestinal epithelial cells. In addition, CNF1 modifies intestinal permeability by directly altering tight junctions’ distribution in 2D Caco-2 monolayers, and by hindering the differentiation of 3D Caco-2 spheroids with an irregular arrangement of these junctions. In vivo, repeated intrarectal administration of CNF1 induces the formation of dysplastic aberrant crypt foci (ACF), and produces the formation of colorectal adenomas in an IBD model. These effects are accompanied by the increased neutrophilic infiltration in colonic tissue, by a mixed pro-inflammatory and anti-inflammatory cytokine milieu, and by the pro-tumoral modulation of the fecal microbiota. Conclusions Taken together, our results support the hypothesis that the CNF1 toxin from E. coli plays an active role in colorectal carcinogenesis. Altogether, these findings not only add new knowledge to the contribution of bacterial toxins to CRC, but also pave the way to the implementation of current screening programs and preventive strategies.